Execution of public policy for the victims of the armed conflict in Suesca - Cundinamarca (2019)
This document, recall one of the most important events of the Colombian political situation and what has appeared from it. The Peace Agreement, signed between the Colombian State, headed by ex-president Juan Manuel Santos Calderón and the group outside the FARC law - Revolutionary Armed Forces of Colombia -, in which a series of benefits are contemplated in favor of the actors that have been linked to the conflict dynamics exerted by the Farc around six decades. As a result, one of the most representative points of the Agreement, lies in the comprehensive reparation of all the victims of the armed conflict, what was generated the design and implementation of what is called Public Policy for Victims of Armed Conflict (PPV). However, taking into account that the internal armed conflict occurred in different ways around the national territory, it implies a differentiation in the execution of the PPV, therefore, it will be reflected in here, the behavior of it, in the municipality of Suesca, during the current government period, it means, from 2016 to 2019, in order to analyze the performance of the territorial entity with respect to the budget execution what is assigned to the assistance of the victims residing in the municipality.